Pengaruh Akuntansi Forensik, Audit Investigatif, Dan Independensi Auditor Terhadap Pengungkapan Fraud - Khofidah Pujilestari; Nera Marinda Machdar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This article examines the influence of forensic accounting, investigative auditing, and auditor independence on fraud disclosure. The aim is to create a hypothesis regarding the influence of each variable that will be used in future research. The results of this literature review are: Forensic Accounting, Investigative Auditing, and Auditor Independence influence Fraud Disclosure.